2 dimension woven kenaf reinforced unsaturated polyester composite - Saiman, Mohd Fahmi (2014)
In recent years, natural fiber from vegetables such as hemp, sisal, ramie, jute and kenaf has been recognized and studied by many researchers due to its potential as an alternative material for synthetic fibers in composite application. Kenaf fiber is a potential reinforced material for composite due to its acceptable properties and supported by the development in Malaysian Kenaf cultivation. Previous studies have demonstrated that Kenaf fibers were recognized in several applications such as automotive component, panel board, packaging, filter material and industrial paper. However, the reinforcement of the fibers is in random, unidirectional and particle form. Therefore, this research is focusing on the composites woven structural preform from the kenaf fiber assisted with the use of internal geometry modeling for optimization. The effect of primary parameters, which are the yarns properties, the fabric count and the weave designs were evaluated on it physical and mechanical properties. Different woven design preform (plain, twill 4/4, satin 8/3 and basket 4/4) were fabricated using floor loom and infused with unsaturated polyester resin using vacuum infusion process. The mechanical properties of the composites were measured and showed that satin 8/3 has highest tensile strength of 39MPa and Plain has highest tensile modulus of 2.63GPa, with flexural strength and impact strength of 48MPa and 29kJ/m2 respectively. The use of VIP and UPE show a good infusion of resin between intra yarns but need much lower viscosity on the UPE for inter yarns. The used of 5% sodium hydroxide solution with the application of tension during the treatment enhanced the composite strength of 12%. The stacking sequence and orientation of 0⁰ ,45⁰,0⁰ of the laminate composite had increased the flexural strength and impact strength of 73MPa and of 82MPa respectively. It is recommended to use a plain and satin structure for better infusion in vacuum infusion process